The Value of Nutrition Support Pharmacist Interventions. (18th February 2022) - Salman, Genene; Boullata, Joseph I.
Abstract : The PHarmacist Avoidance or Reductions in Medical Costs in CRITically Ill Adults: PHARM-CRIT Study by Rech et al demonstrated the value of critical care pharmacists' interventions. The services provided by nutrition support pharmacists were briefly mentioned. This article aims to highlight the value of interventions provided by nutrition support pharmacists.